A comparative study for lubrication of surface textured porous journal bearing with two different non-Newtonian fluid models. (2016) - Sharma, Nitin; Sharma, Rajesh Kumar; ,; Kango, Saurabh
A study of two non-Newtonian fluid models viz., power law fluid model and couple stress fluid model on the hydrodynamic lubrication of porous journal bearing has been investigated. In addition, sinusoidal type of surface texturing is incorporated at different configurations on the bearing surface to find the performance of the bearing in both cases. The modified Reynolds equation with Darcy model using Reynolds boundary conditions is solved by central differencing technique of finite difference method. The bearing performance characteristics are calculated numerically and are compared with each other. A direct comparison between the two models has been shown graphically. The power law index (n) has taken in the range 1.0 to 1.2 while couple stress parameter (l*) has taken in the range 0 to 0.6. Numerical results show that both models significantly improve the load carrying capacity (W) and reduce coefficient of friction (COF). The results are more effective for low eccentricity ratios instead of high eccentricity ratios. It has also been observed for surface texturing that configuration 3 (72° to 144°) gives optimum results for both load carrying capacity as well as COF, when compared with all other configurations.